2015
DOI: 10.1111/basr.12075
|View full text |Cite
|
Sign up to set email alerts
|

Doing Well by Reporting Good: Reporting Corporate Responsibility and Corporate Performance

Abstract: This article aimed to examine the impacts of reportingtype corporate responsibility activities (CRA-R) on corporate social and financial performance. Academic research has explored how varying attributes of markets, industry sectors and firms might shape corporate social and financial performance, but includes little effort to examine the impacts of different kinds of CRA on corporate performance. We build on debate about the value of firms' reporting activities related to corporate responsibility. Recent lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…Activities such as donations are equated with community investment and waste management costs are assimilated to environmental protection expenditures. Thus, non-financial reporting plays an increasingly important role and aims to increase transparency and performance [16,17], as well as to encourage companies to adopt a more sustainable business strategy [18].…”
Section: Introductionmentioning
confidence: 99%
“…Activities such as donations are equated with community investment and waste management costs are assimilated to environmental protection expenditures. Thus, non-financial reporting plays an increasingly important role and aims to increase transparency and performance [16,17], as well as to encourage companies to adopt a more sustainable business strategy [18].…”
Section: Introductionmentioning
confidence: 99%
“…They found that firm performance was positively related to the extent of economic benefits as a result of participating in the UNGC. Lee and Maxfield () analyze the impacts of reporting corporate responsibility activities (CRA‐R) on corporate social performance (CSP) and corporate financial performance (CFP). Using a dataset of U.S. corporations selected in the Fortune 500 their empirical evidence suggests that CRA‐R impacts CSP for secondary stakeholders and also CFP.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of sustainability reports and their association with financial performance appears more questionable. As noted by Lee and Maxfield (, p. 577), much recent literature has concluded that corporate sustainability reporting is little more than “superficial marketing,” and recent studies suggest that the link between CSR reporting and financial performance may be relatively weak. For instance, Kaspereit and Lopatta () found a positive association between environmental performance and financial performance, but the link between environmental reporting and financial performance was weaker and its significance depended on model specification.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…These early studies provided important insights into managers' attitudes towards sustainability reporting, and the prescriptions offered appeared reasonable at the time. However, recent studies have concluded that corporate sustainability reports are little more than superficial window dressing (e.g., Lee & Maxfield, ). Consequently, we feel that research addressing fundamental questions regarding the determinants of practicing managers' attitudes towards sustainability reporting is clearly called for (cf.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%